SUB-ACUTE TOXICITY TEST OF ULTRAVIOLET C (UVC)-IRADIATED FOOD ON WHITE RATS (Rattus novergicus) WISTAR STRAIN - Achmadi, Achmadi; septiani, septiani; safari, wulan fitriani (Universitas Muhammadiyah Metro, 2024)
Food Loss and Waste (FLW) is a global problem that has a negative impact on various sectors of life. Microbial spoilage of food products is a major contributor to food waste. Ultraviolet C (UVC) radiation is an effective method for inactivating spoilage microorganisms. Until now, there is no research about effect of UVC on the toxicity of food products and the effects of consuming food products that have been irradiated with UVC, so this research was conducted to determine the toxicity of consuming food that has been irradiated with UVC. Toxicity testing used Rattus norveginus of the Wistar strain weighing 200-300 into 2 groups (n=3), control group (feedd not irradiated) and treatment group (feed irradiated for 1 hour). Feeding is carried out for 45 days. Blood samples were taken from the rats heart and hemoglobin levels, leukocyte counts, SGOT and SGPT levels were measured. The results showed in the control group the hemoglobin level 6.96 g/dL, the leukocyte count 6.9 x 103/uL, the SOGT level 85.5 U/ and the SGPT level 44 U/L, in the treatment group the hemoglobin level 7.94 g/ dL, leukocyte count 15.63 x 103/uL, SOGT level 81.3 U/ and SGPT level 49.6 U/L.